Cross-section Morphology of the Scratch-Induced Cracks in Soda-Lime-Silica Glass - Matsuoka, Jun; Guo, Danwei; Yoshida, Satoshi (Frontiers in Materials, 2017)
Scratch-induced cracking is a serious problem for the use of glass products. At the scratch process, both median (vertical to the glass surface) and lateral (horizontal to the glass surface) cracks are formed. In this study, morphology of the scratch-induced cracks in a commercial soda-lime-silica glass was investigated by the scanning electron microscopy for the specimen broken across the scratch groove. Scratch test was carried out using a Knoop indenter in water and in dehydrated heptane. When scratch speed was 70 x 10-6 ms-1, length of both vertical and horizontal cracks was proportional to the normal load at scratching, and environmental dependence was not observed. When scratch speed was increased with the constant normal load of 200g, length of both cracks was decreased. In the case of horizontal crack, no environmental effect was observed. On the other hand, length of the vertical crack scratched in water was much longer than that in heptane. At very high scratch speed as high as 1000 x 10-6 ms-1, no vertical crack was formed in the heptane. These differences between horizontal and vertical cracks should be due to the differences of crack initiation position and the influence of subcritical crack growth to these cracks.